Nutritive qualities of patties prepared with mixture of meat and oyster mushroom - Wan Rosli, W. I.; Solihah, M.A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Nutritive qualities of patties prepared from chicken, beef and oyster mushroom were determined. Three groups of rats were fed with patty diets prepared with either a combination of 75% chicken + 25% oyster mushroom (CMP) or 75% beef + 25% oyster mushroom (BMP) or 100% chicken patty + 0% oyster mushroom (CP). There was no significant difference (P < 0.05) in total tryglyceride (0.3-0.5 mmol/L), total cholesterol (1.7-1.9 mmol/L) LDL-cholesterol (0.3-0.4 mmol/L) and HDL-cholesterol (1.2-1.4 mmol/L) for all groups except for protein free. Protein effeciency ratio (PER) values of CMP and BMP groups were significantly lower than casein group but significantly higher than chicken patty (CP) group. Both CMP and BMP fed groups recorded PER values at 1.73 and 1.69 while CP had PER value at 1.52. The AD of rats fed with CMP, BMP and CP diets were closely ranged from 98.3-98.9% but not significant as compared to casein diet group (98.5%). The close AD values between CMP, BMP and CP indicated that the mixture of patty protein from either chicken or beef with protein of oyster mushroom did not affect digestibility aspect. In summary, addition of oyster mushroom into either chicken or beef patties did not changed AD but improved PER value, thus proving that oyster mushroom could be used as an alternative ingredient to replace meat partially in the making of patties.